CIDADANIA E RELAÇÕES DE CONSUMO NO CENTRO DE COMÉRCIO POPULAR DE PONTA GROSSA: UM OLHAR ETNOGRÁFICO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
This dissertation deals with the dynamic relationships between citizenship and consumption processed at Centro de Comércio Popular de Ponta Grossa (PR) (CCP), public space for urban consumption. The CCP is a popular market, created in 2002 that relocated informal traders who worked at the João Pessoa Square, in Ponta Grossa. With the relocation, merchants gained access to a new consumer space, public and formalized, although reminiscences of the past of the Square still exist, especially in the dimensions of the legality of the products offered. However,beyond a simple space of consuming, CCP revealed hostile environment mediations between merchants and the public sphere, while constituting a micro environment in which consumption relations are central columns and plural social relations are adjacent practices in the construction of meaning in the social relations of their subjects. The research presented consists of a qualitative research in social sciences, a phenomenology research, which includes ethnographic practice.
Keywords: cidadania; relações de consumo; centro de comércio popular de Ponta Grossa; etnografia; citizenship; practices of consumption; centro de comércio popular de Ponta Grossa; ethnography; CNPQ::CIENCIAS SOCIAIS APLICADAS